The analysis level of optimism that influence investor’s risk tolerance in asset allocation - Siti Nazifah Zainol Abidin; Saiful Hafizah Jaaman; Ahmad Syafadhli Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Investor’s risk of tolerance level has been widely categorized into three types, namely, risk averse, risk seeker and risk neutral. Nevertheless, in assessing the risk of a particular asset, investors that fall under the same risk tolerance classification may have different levels of optimism. It is thus beneficial to complement types of investor’s risk of tolerance with level of optimism. In this study, a fuzzy asset allocation model that satisfy heterogeneous investor’s risk of tolerance with regards to investor’s level of optimism is proposed. Enhancing Fuzzy Inferences System (FIS) with cooperation of optimism level, this study obtains a flexible fuzzy allocation model which is based on heterogeneous types of investor’s risk of tolerance combined with various level of optimism. Empirical evidence on 30 Malaysian shares employing the model developed shows that the proposed model successfully able to differentiate various combinations of investor’s risk of tolerance level and investor’s level of optimism. Furthermore, model is able to determine asset allocation and priority shares for each combination accordingly. In conclusion, it is shown that employing the proposed model allows investor to make beneficial investment decision according to his combined risk tolerance and level of optimism.